Prevalence and Prognosis of Familial Hypercholesterolemia in Patients With Acute Coronary Syndrome in Mie Prefecture, Japan ― Report From Mie ACS Registry - Takasaki, Akihiro; Kurita, Tairo; Masuda, Jun; Hoshino, Kozo; Seko, Tetsuya; Tanigawa, Takashi; Kitamura, Tetsuya; Ichikawa, Takehiko; Ito, Masaaki; Dohi, Kaoru (Circulation Journal, 2020)
Background:Familial hypercholesterolemia (FH) is an autosomal dominant disorder characterized by elevated low-density lipoprotein cholesterol concentration and premature acute coronary syndrome (ACS). However, hereditary diseases may have regional characteristics, and few data are available regarding the prevalence of FH throughout particular regions in Japan. This study investigated the prevalence and prognosis of FH in patients with ACS in Mie Prefecture, Japan.Methods and Results:This study investigated 738 ACS patients from the Mie ACS Registry in Mie Prefecture, and 706 (95.7%) with sufficient data to diagnose FH were enrolled for analysis. Eighteen patients (2.5%) were diagnosed with FH, which was similar to findings of another multidistrict registry conducted in Japan. Patients with FH were significantly younger and had a higher prevalence of premature onset of ACS than patients with non-FH (P<0.01). Incidence of major adverse cardiac and cerebrovascular events (MACCE) was not statistically different between patients with FH and non-FH in this study population, even in the propensity score-matched analysis.Conclusions:Prevalence of FH in ACS patients from the Mie Prefecture was similar to that found in another Japanese multidistrict registry. Among ACS patients, short-term incidence of MACCE was not statistically different between patients with FH and non-FH in this study population.